Recursive intergenerational utility in global climate risk modeling - Ha-Duong Minh; Nicolas Treich (Fondazione Eni Enrico Mattei (FEEM), 1999)
This paper distinguishes relative risk aversion and resistance to intertemporal substitution in climate risk modelling. Stochastic recursive preferences are introduced in a stylised numeric climate-economy model using preliminary IPPC 1998 scenarios. It shows that higher risk aversion increases the optimal carbon tax. Higher resistance to intertemporal substitution alone has the same effect as increasing the discount rate, provided that the risk is not too large. We discuss implications of these findings for the debate upon discounting and sustainability under uncertainty.
Keywords: Q20; D81; D90; H43; 330; Recursive utility; risk; discounting; sustainability; climate; Umweltbewertung; Klimawandel; Risikoaversion; Zeitpräferenz; Generationengerechtigkeit; Ökosteuer; Theorie